2017
DOI: 10.1159/000485595
|View full text |Cite
|
Sign up to set email alerts
|

Cuff-Based Oscillometric Central and Brachial Blood Pressures Obtained Through ABPM are Similarly Associated with Renal Organ Damage in Arterial Hypertension

Abstract: Background/Aims: Central blood pressure (BP) has been suggested to be a better estimator of hypertension-associated risks. We aimed to evaluate the association of 24-hour central BP, in comparison with 24-hour peripheral BP, with the presence of renal organ damage in hypertensive patients. Methods: Brachial and central (calculated by an oscillometric system through brachial pulse wave analysis) office BP and ambulatory BP monitoring (ABPM) data and aortic pulse wave velocity (PWV) were measured in 208 hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In our study, central BP had no better association with renal impairment than peripheral BP, a finding that corroborates with those of previous outpatient studies ( 42 , 43 ). This may be justified by the fact that central BP is associated with macrovascular damage, but is not so closely related to microvascular injury, typical of renal injury ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, central BP had no better association with renal impairment than peripheral BP, a finding that corroborates with those of previous outpatient studies ( 42 , 43 ). This may be justified by the fact that central BP is associated with macrovascular damage, but is not so closely related to microvascular injury, typical of renal injury ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
“…Another study reported the better predictive value of central BP compared to peripheral BP for cardiac damage such as LVH (38). A possible explanation is that arterial stiffness increases systolic BP, causing an early return of pulse waves during the systolic period and increased left ventricle afterload that causes cardiac hypertrophy and consequent LVH (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent study in which the central blood pressure in patients with CKD stage 3 and albuminuria were compared with matched patients with no CKD, there were no significant differences found regarding the central blood pressure parameters between these two groups of patients [27], suggesting that the impact of kidney function on central BP may only be present in more advanced CKD [28]. This also raises a question concerning the importance of targeting these parameters in early stages of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…[24] One recent study, central BP in patients with CKD stage 3 and albuminuria were compared with matched patients without CKD, and there were no significant differences of central BP parameters between these two groups of patients[25] like us and suggested that the kidney function has impact of on central BP, may be only in more advanced CKD. [26] This also raises a question concerning the importance of targeting these parameters in early stages of CKD.…”
Section: Discussionmentioning
confidence: 99%